Justice, community, and dialogue in international relations - Shapcott, Richard (Cambridge studies in international relations, 2001)
Shapcott considers the issue of cultural diversity and international morality. Conversation, and our ability to understand each other despite differences, provide the basis for the development of a world-wide, cosmopolitan, moral community. Students and scholars of international relations, politics and philosophy will be interested in this original study.